Penerapan Evidence Based Practice Terapi Cermin untuk Meningkatkan Fungsi Motorik Ekstremitas Atas pada Pasien Stroke - Rohani, Rohani; Jumaiyah, Wati; Yunitri, Ninik; Agung, Rizki Nugraha; Agustina, Elis Nurhayati (Universitas Malahayati, 2024)
ABSTRACT The incidence of stroke throughout the world is currently becoming increasingly worrying, not only as the main cause of death, but also ranked second as a cause of global disability with more than 13 million new cases each year. A number of intervention measures have been carried out to overcome the physical limitations of the upper extremities in post-stroke patients, such as training the paralyzed arm, carrying out arm exercises that focus on the disorder experienced, applying functional stimulation using electricity, carrying out rehabilitation assisted by robots, and undergoing bilateral arm training. However, all of these interventions require a high level of intensity as well as “1 to 1” interaction with a therapist over several weeks, which makes it difficult for patients to maintain an intensive level of therapy. To carry out mirror therapy with the aim of increasing muscle strength in parts of the body that experience weakness due to stroke, especially upper extremity hemiparesis. This research is a cross-sectional study. The study population consisted of stroke patients with upper extremity hemiparesis who were undergoing inpatient treatment on the seventh floor of the National Brain Center Hospital. The sample size was calculated taking into account the effect size of 0.67, significance level of 0.05, power of 80%, and risk of dropping out of 20%. Thus, the number of participants in this study was 24 patients. Mirror therapy has been proven to be successful in increasing muscle strength in stroke patients with upper limb hemiparesis at PON Hospital. This therapy is carried out for 30 minutes, five days a week, for three weeks (8-31 May 2023). Mirror therapy can be carried out easily by nurses and involves the patient's family. Mirrors are available in each treatment room to make carrying out therapy easier. The study findings showed an increase in muscle strength in the upper extremities, confirming the effectiveness of mirror therapy in stroke patients with hemiparesis. Keywords Evidance Based Practice Mirror Therapy, Extremity Motor Function, Stroke Patients. ABSTRAK Kejadian stroke di seluruh dunia saat ini menjadi semakin mengkhawatirkan, tidak hanya sebagai penyebab utama kematian, tetapi juga menduduki peringkat kedua sebagai penyebab kecacatan global dengan lebih dari 13 juta kasus baru setiap tahunnya. Sejumlah tindakan intervensi telah dilakukan untuk mengatasi keterbatasan fisik ekstremitas atas pada pasien paska stroke, seperti melatih lengan yang mengalami paralisis, melakukan latihan lengan yang difokuskan pada gangguan yang dialami, menerapkan stimulasi fungsi menggunakan listrik, melakukan rehabilitasi dibantu oleh robot, dan menjalani pelatihan lengan bilateral. Namun, semua intervensi tersebut memerlukan tingkat intensitas yang tinggi serta interaksi